2012
DOI: 10.1111/j.1439-0272.2012.01324.x
|View full text |Cite
|
Sign up to set email alerts
|

Terazosin-induced alterations in catalase expression and lipid peroxidation in the rat seminal vesicles

Abstract: Previous studies have shown that alpha1-adrenergic receptor antagonists may alter seminal vesicle contractility and impair fertility in male rats. This study was designed to investigate the effects of terazosin on the catalase expression in the seminal vesicles and the lipid peroxidation of the seminal fluid in normal adult rats. Wistar rats were treated with terazosin (1.2 mg kg(-1) body weight, given orally every second day) for 120 days. Catalase expression was assessed immunohistochemically in tissue secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
(83 reference statements)
1
3
0
2
Order By: Relevance
“…Additionally, the expressions of many ion channel proteins and total proteins including fructosamine, ALT, AST and PSA in seminal tissues and others could be decreased via HDAC inhibition which is a VPA property. The increase in the MDA levels in seminal vesicle treated with VPA was similar to that of rat seminal vesicle induced with terazosin (Mitropoulos et al, ). It has been shown that increased MDA levels in seminal plasma were significantly associated with the decreases in sperm count, normal morphology and motility in infertile men (Colagar, Pouramir, Marzony, & Jorsaraei, ; Khosrowbeygi & Zarghami, ) Taken together, our results indicate that VPA may lower the quality of seminal plasma, resulting in male infertility.…”
Section: Discussionsupporting
confidence: 70%
“…Additionally, the expressions of many ion channel proteins and total proteins including fructosamine, ALT, AST and PSA in seminal tissues and others could be decreased via HDAC inhibition which is a VPA property. The increase in the MDA levels in seminal vesicle treated with VPA was similar to that of rat seminal vesicle induced with terazosin (Mitropoulos et al, ). It has been shown that increased MDA levels in seminal plasma were significantly associated with the decreases in sperm count, normal morphology and motility in infertile men (Colagar, Pouramir, Marzony, & Jorsaraei, ; Khosrowbeygi & Zarghami, ) Taken together, our results indicate that VPA may lower the quality of seminal plasma, resulting in male infertility.…”
Section: Discussionsupporting
confidence: 70%
“…We assumed that low quality of SVF in CS was caused from secreting imbalance of essential substance levels. The increase in lipid peroxidation like MDA level has shown the seminal plasma of infertile males with different reproductive problems (Collodel et al, 2015;Mitropoulos et al, 2013;Tavilani, Doosti, & Saeidi, 2005). In addition, the increased MDA level in seminal plasma has been demonstrated to relate with the decreases in F I G U R E 3 Expression of heat-shock protein 70 (Hsp70) revealed by Western blotting (a and b) and expression intensity (c and d) in seminal vesicle lysate and fluid compared between control (Con) and chronic stress (CS) groups respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For the first time, we have demonstrated the effect ofMTX on thickness of seminal vesicle epithelia and changes of testicular tyrosine phosphorylated proteins. The low epithelia thickness of seminal vesicle could cause abnormal secreting of seminal fluid including catalase expression and lipid peroxidation (Mitropoulos et al, 2013). The tyrosine phosphorylation in the testis is assumed to be essential for spermatogenesis and testosterone production.…”
Section: Discussionmentioning
confidence: 99%